Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Pegawai di Kantor Camat Kecamatan Tuhemberua Kabupaten Nias Utara - Zega, Yamolala; Lase, Heseziduhu (Jurnal Sains dan Teknologi, 2023)
This study aims to find out how the work motivation of employees in the Tuhemberua Office of North Nias Regency and to determine the level of performance of employees in the Tuhemberua Office of North Nias Regency. The research was conducted on 16 employees in the company. The research was conducted by means of observation, interviews and questionnaires which were distributed to 16 people. The questionnaire that was distributed consisted of 4 alternative answer options. The research results show that the work motivation of employees at work. It turns out that the motivation of each employee is different, some are motivated to get a good working career, some are motivated to get recognition and appreciation, there are also employees who are only motivated because of the wages and incentives they will get. However, these different motivations can encourage employees to work better. In general, employees at the Tuhemberua Office of North Nias Regency have good performance, where every workload and task given can be carried out properly. From observation and processing of data, especially questionnaires answered by respondents who were employees at the Tuhemberua Office of North Nias Regency, as many as 16 respondents, the researchers suggested that there was an influence of work motivation on employee performance at the Tuhemberua Office of North Nias Regency with a contribution of 24.8% and the rest determined by variables or other factors.